Empowering Frontline Nurses as Implementation Science Leaders. - Al-Moteri, Modi (Journal of Nursing Care Quality)
Background: Sustaining evidence-based practice (EBP) in nursing faces systemic and workforce barriers. Implementation science (IS) offers structured approaches to support EBP integration. Under Saudi Arabia's Vision 2030, scalable nurse-led models are critical to bridging the research-to-practice gap. Aim: To evaluate the Evidence-Based Quality Improvement Project (EQUIP), a nurse-led model grounded in IS, by assessing its implementation through frontline implementation lead (IL) nurses. Methods: A mixed-methods formative evaluation was conducted across multiple healthcare facilities. Two IL nurse-led quality improvement (QI) projects were used as illustrative examples. Data sources included QI documentation, clinical metrics, and researcher field notes. Results: EQUIP enabled IL nurses to apply EBP in routine care and proved adaptable across diverse settings. However, inconsistent engagement and competing workload demands were the most influential barriers, underscoring the need for structured support. Conclusion: EQUIP presents a scalable IS-based initiative to embed EBP in nursing. Institutional support is essential for sustained implementation.